A phase change toughened amorphous composite material and a preparation method and application thereof

CN118007036BActive Publication Date: 2026-10-30SONGSHAN LAKE MATERIALS LAB
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211388622.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-08
Publication Date
2026-10-30
Estimated Expiration
2042-11-08

AI Technical Summary

Technical Problem

[0004]本申请的目的在于提供一种大尺寸相变增韧非晶复合材料及其制备方法和应用,其旨在改善现有的非晶复合材料的临界形成尺寸较小,初生相极易联结长大且空间分布不均匀的技术问题

Benefits of technology

[0048]为使本申请实施例的目的、技术方案和优点更加清楚,下面将对本申请实施例中的技术方案进行清楚、完整地描述。实施例中未注明具体条件者,按照常规条件或制造商建议的条件进行。所用试剂或仪器未注明生产厂商者,均为可以通过市售购买获得的常规产品。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118007036B_ABST
    Figure CN118007036B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of amorphous composite materials, in particular to a phase change toughened amorphous composite material and a preparation method and application thereof. The atomic percentage expression general formula of the phase change toughened amorphous composite material is (Cu a M d )(Zr b N e )Al c ; in the atomic percentage expression general formula, M is at least one selected from Ag, Pt, Pd, Co, Ni, Fe, Au, Si and Sn, N is at least one selected from Ti, Hf, Nb, Ta, Y, Sc and Ga, 35<=a<=60, 35<=b<=60, 1<=c<=10, 0.01<=d<=10, 0.01<=e<=10, and a+d=b+e, a+b+c+d+e=100. The phase change toughened amorphous composite material provided in the application can form columnar materials with a diameter size reaching a centimeter level on the basis of keeping high compressive plasticity and work hardening capacity, and the application range of the amorphous composite material is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of amorphous composite materials technology, and more specifically, to a phase transformation toughened amorphous composite material, its preparation method, and its application. Background Technology

[0002] Amorphous alloys, with their unique microscopic atomic arrangement characteristics of "long-range disorder and short-range order," have superior properties compared to crystalline alloys, such as high strength, high hardness, good wear resistance, and good corrosion resistance. They have broad application prospects in industries such as aviation, aerospace, IT electronics, machinery, and chemicals.

[0003] However, due to the lack of dislocation deformation mechanisms in conventional crystalline materials, amorphous alloys suffer from bottleneck problems such as room temperature brittleness and strain softening, which greatly limits their application. Summary of the Invention

[0004] The purpose of this application is to provide a large-size phase transformation toughened amorphous composite material, its preparation method and application, which aims to improve the technical problems of existing amorphous composite materials with small critical formation size, easy bonding and growth of primary phase and uneven spatial distribution.

[0005] Firstly, this application provides a phase transformation toughened amorphous composite material, wherein the atomic percentage expression formula of the phase transformation toughened amorphous composite material is (Cu a M d (Zr) b N e Al c In the general formula for expressing atomic percentages, M is selected from at least one of Ag, Pt, Pd, Co, Ni, Fe, Au, Si, and Sn, and N is selected from at least one of Ti, Hf, Nb, Ta, Y, Sc, and Ga. 35≤a≤60, 35≤b≤60, 1≤c≤10, 0.01≤d≤10, 0.01≤e≤10, and a+d=b+e, a+b+c+d+e=100.

[0006] In the atomic percentage expression formula of the phase transformation toughened amorphous composite material provided in this application, Cu and Zr can form an austenitic B2-CuZr phase, which enables the amorphous composite material to have the B2-CuZr phase as the in-situ primary crystalline phase. This is beneficial for the amorphous composite material to have both compressive plasticity and work hardening ability.

[0007] M, N, and Al elements can effectively reduce the nucleation rate and growth rate of the B2 phase, making it less likely for the metastable primary crystalline phase (B2 phase) to aggregate and grow during the solidification step of the preparation process. This results in the B2 phase forming a fine and dispersed microstructure in the amorphous matrix, leading to a more uniform spatial distribution of the crystalline phase in the amorphous composite material (i.e., a more uniform microstructure distribution), which is beneficial for further improving the mechanical properties of the amorphous composite material. M, N, and Al elements can also improve the amorphous forming ability of the alloy material, increasing the critical formation size of the amorphous composite material. This is beneficial for preparing cylindrical phase transformation toughened amorphous composite materials with larger diameters (reaching the centimeter scale), greatly expanding the application range of amorphous composite materials.

[0008] In some embodiments of the first aspect of this application, the atomic percentage is expressed in the general formula as follows: 40≤a≤45, 40≤b≤45, 2≤c≤6, 6≤d≤8, and 1≤e≤8.

[0009] Under the above conditions, it is beneficial to further improve the compressive plasticity, work hardening ability and critical formation size of phase transformation toughened amorphous composite materials, which greatly expands the application range of amorphous composite materials.

[0010] In some embodiments of the first aspect of this application, the atomic percentage expression for the phase transformation toughened amorphous composite material is (Zr 42 Ti5Hf1)(Cu 40.75 Ag5Co 0.5 Ni1Sn 0.75 Al4、(Zr 44 Ti2Hf 0.5 (Cu) 42.75 Ag5Co 0.5 Ni 0.5 Sn 0.75 Al4、(Zr 41.5 Ti5Hf1Nb 0.5 (Cu) 40.75 Ag5Co 0.5 Ni1Sn 0.75 Al4 or (Zr 42 Ti5Hf 0.5 Nb 0.5 (Cu) 41.5 Ag5Co 0.5 Ni 0.5 Sn 0.5 )Al4.

[0011] The aforementioned phase change toughened amorphous composite materials have good compressive plasticity and work hardening ability, as well as a large critical formation size, which greatly expands the application range of amorphous composite materials.

[0012] In some embodiments of the first aspect of this application, the phase change toughened amorphous composite material is cylindrical, and the diameter of the phase change toughened amorphous composite material is ≥10mm.

[0013] In some embodiments of the first aspect of this application, the compression ratio of the phase change toughened amorphous composite material is 4-9%.

[0014] In a second aspect, this application provides a method for preparing a phase transformation toughened amorphous composite material as provided in the first aspect above, comprising: melting and mixing raw materials according to a general formula expressed in atomic percentage under an inert atmosphere, injecting the mixture into a mold, and then cooling it.

[0015] According to the atomic percentage expression formula provided in this application, the phase change toughened amorphous composite material prepared by the above method can be made to form columnar materials with diameters reaching the centimeter level while maintaining certain compressive plasticity and work hardening ability, thus expanding the application range of amorphous composite materials.

[0016] In some embodiments of the second aspect of this application, the temperature of the mold is 10-25°C.

[0017] The temperature of the mold is 10-25℃, which is conducive to the rapid solidification of the molten raw material mixture and the formation of amorphous phase and B2-CuZr crystalline phase during the solidification process. This is beneficial to further improve the compressive plasticity and work hardening ability of the phase transformation toughened amorphous composite material, and also to improve the critical formation size of the amorphous composite material. This results in a larger size of the prepared amorphous composite material, which greatly expands the application range of amorphous composite materials.

[0018] Optionally, the mold is a copper mold.

[0019] Copper molds have good thermal conductivity, which is conducive to the rapid solidification of molten raw material mixtures and the formation of amorphous phases and B2-CuZr crystalline phases during the solidification process. This helps to improve the critical formation size of amorphous composite materials, resulting in larger sizes of the prepared amorphous composite materials and greatly expanding the application range of amorphous composite materials.

[0020] In some embodiments of the second aspect of this application, the melting and mixing step includes: melting the raw materials to prepare a master alloy ingot under vacuum and an inert atmosphere; and then, under an inert atmosphere of 0.01-0.05 MPa, arc melting the master alloy ingot with a current of ≥240 A and holding it at that temperature for 5-20 s.

[0021] Under the above conditions, the raw materials can be fully melted and mixed evenly, which is beneficial to further improve the compressive plasticity, work hardening ability and critical formation size of phase transformation toughened amorphous composite materials, and improve the degree of B2 phase dispersion.

[0022] In some embodiments of the second aspect of this application, the step of preparing the master alloy ingot includes: melting the raw materials sequentially in order of decreasing melting point.

[0023] Melting the raw materials sequentially in order of decreasing melting point can prevent the lower melting point raw materials from melting first and then coating the surface of the higher melting point raw materials, which would result in insufficient melting of the higher melting point raw materials. This is beneficial to improving the uniformity of mixing between the raw materials, which in turn helps to further improve the compressive plasticity, work hardening ability and critical formation size of the obtained phase transformation toughened amorphous composite material, and improve the degree of B2 phase dispersion.

[0024] Optionally, the melting current for preparing the master alloy ingot is ≥240A.

[0025] Optionally, the vacuum degree for preparing the master alloy ingot is 5 × 10⁻⁶. -3 -5×10 -4 Pa.

[0026] Thirdly, this application provides an application of the phase change toughened amorphous composite material provided in the first aspect above in the preparation of harmonic reducer gears, 3C electronic structural parts, armor-piercing heads or armor plates. Attached Figure Description

[0027] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1 A process flow diagram for preparing the phase transformation toughened amorphous composite material provided in this application is shown.

[0029] Figure 2 The X-ray diffraction pattern of the phase transformation toughened amorphous composite material of Example 1 of this application is shown.

[0030] Figure 3 The SEM image of the phase transformation toughened amorphous composite material of Embodiment 1 of this application is shown.

[0031] Figure 4 The X-ray diffraction pattern of the phase transformation toughened amorphous composite material of Example 2 of this application is shown.

[0032] Figure 5 The SEM image of the phase transformation toughened amorphous composite material of Embodiment 2 of this application is shown.

[0033] Figure 6The X-ray diffraction pattern of the phase transformation toughened amorphous composite material of Example 3 of this application is shown.

[0034] Figure 7 The SEM image of the phase transformation toughened amorphous composite material of Example 3 of this application is shown.

[0035] Figure 8 The X-ray diffraction pattern of the phase transformation toughened amorphous composite material of Example 4 of this application is shown.

[0036] Figure 9 The SEM image of the phase transformation toughened amorphous composite material of Example 4 of this application is shown.

[0037] Figure 10 The X-ray diffraction pattern of the amorphous composite material of Comparative Example 1 of this application is shown.

[0038] Figure 11 An optical mirror image of the amorphous composite material of Comparative Example 1 of this application is shown.

[0039] Figure 12 The X-ray diffraction pattern of the amorphous composite material of Comparative Example 2 of this application is shown.

[0040] Figure 13 An optical mirror image of the amorphous composite material of Comparative Example 2 of this application is shown.

[0041] Figure 14 The diagram shows the compressive engineering stress-strain curve of the phase change toughened amorphous composite material of Embodiment 1 of this application.

[0042] Figure 15 The diagram shows the compressive engineering stress-strain curve of the phase change toughened amorphous composite material of Embodiment 2 of this application.

[0043] Figure 16 The diagram shows the compressive engineering stress-strain curve of the phase change toughened amorphous composite material of Embodiment 3 of this application.

[0044] Figure 17 The diagram shows the compressive engineering stress-strain curve of the phase transformation toughened amorphous composite material of Embodiment 4 of this application.

[0045] Figure 18 The stress-strain curve of the amorphous composite material of Comparative Example 1 of this application is shown.

[0046] Figure 19 The stress-strain curve of the amorphous composite material of Comparative Example 2 of this application is shown.

[0047] Figure 20The nanoindentation curve of the B2 crystalline phase of the phase transformation toughened amorphous composite material of Example 4 of this application is shown, as well as the hardness and modulus diagrams of the B2 crystalline phase and the amorphous matrix. Detailed Implementation

[0048] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0049] This application provides a phase transformation toughened amorphous composite material, wherein the atomic percentage expression formula of the phase transformation toughened amorphous composite material is (Cu a M d (Zr) b N e Al c In the general formula for expressing atomic percentages, M is selected from at least one of Ag, Pt, Pd, Co, Ni, Fe, Au, Si, and Sn, and N is selected from at least one of Ti, Hf, Nb, Ta, Y, Sc, and Ga. 35≤a≤60, 35≤b≤60, 1≤c≤10, 0.01≤d≤10, 0.01≤e≤10, and a+d=b+e, a+b+c+d+e=100.

[0050] In the atomic percentage expression formula of the phase transformation toughened amorphous composite material provided in this application, Cu and Zr can form an austenitic B2-CuZr phase, which enables the amorphous composite material to have the B2-CuZr phase as the in-situ primary crystalline phase and to exhibit a dispersed and uniform distribution. This is beneficial for the amorphous composite material to have both certain compressive plasticity and work hardening ability.

[0051] This application limits the selection of M element to at least one of Ag, Pt, Pd, Co, Ni, Fe, Au, Si, and Sn, and the selection of N element to at least one of Ti, Hf, Nb, Ta, Y, Sc, and Ga, and limits the elemental ratio between M element, N element, Al, Cu, and Zr. It can influence the microstructure characteristics of the B2-CuZr phase, such as composition, shape, volume fraction, size, and grain orientation, through M element, N element, and Al.

[0052] Specifically, element M has chemical similarity to Cu in the B2-CuZr phase, and its main role is to replace the Cu atoms in the simple cubic ordered lattice during the formation of the B2 phase. Element N has chemical similarity to Zr in the B2-CuZr phase, and its main role is to replace the Zr atoms in the simple cubic ordered lattice during the formation of the B2 phase. The partial replacement of Cu and Zr sites in the B2-CuZr phase by elements M and N can enhance the stability of the alloy liquid during the preparation of the transformation-toughened amorphous composite material (i.e., lower the liquidus temperature, or make the liquidus temperature approach the eutectic temperature, etc.), reduce the diffusion coefficient of the liquid phase, and improve the amorphous forming ability of the alloy material. This results in an increase in the critical formation size of the amorphous composite material and the degree of B2 phase dispersion, which is beneficial for preparing columnar transformation-toughened amorphous composite materials with larger diameters (reaching centimeter-level dimensions).

[0053] M, N, and Al can effectively reduce the nucleation rate (i.e., increase the liquid-solid interface energy) and growth rate of the B2 phase, making it less likely for the metastable primary crystalline phase (B2 phase) to grow together during the solidification step of the preparation process. This results in the B2 phase forming a fine, dispersed microstructure in the amorphous matrix, or even causing the B2 phase to precipitate in a cubic or irregular boundary shape. Consequently, the spatial distribution of the crystalline phase in the amorphous composite material becomes more uniform (i.e., the microstructure distribution becomes more uniform), which is beneficial for further improving the compressive plasticity and work hardening ability of the amorphous composite material. M, N, and Al also improve the amorphous formation ability and the dispersion degree of the B2 phase in the alloy material, greatly expanding the application range of amorphous composite materials.

[0054] In addition, the proportions of M, N and Al can take into account the solid solubility of the main components Cu and Zr and avoid deviation from the B2 phase region.

[0055] As an example, in the general formula for expressing the atomic percentage of phase change toughened amorphous composite materials, a can be 35, 40, 42, 45, 50, 55 or 60, etc.; b can be 35, 40, 42, 45, 50, 55 or 60, etc.; c can be 1, 2, 5, 7 or 10, etc.; d can be 0.01, 0.1, 0.5, 1, 2, 5, 7 or 10, etc.; and e can be 0.01, 0.1, 0.5, 1, 2, 5, 7 or 10, etc.

[0056] Understandably, the M element can be selected from one, two, or more elements from Ag, Pt, Pd, Co, Ni, Fe, Au, Si, and Sn; and the N element can be selected from one, two, or more elements from Ti, Hf, Nb, Ta, Y, Sc, and Ga.

[0057] Compared to "the element M is only selected from Ag, Pt, Pd, Co, Ni, Fe,

[0058] The conditions where "the element is selected from one of Au, Si, and Sn, or the element N is selected from only one of Ti, Hf, Nb, Ta, Y, Sc, and Ga" and "the element M is selected from two or more of Ag, Pt, Pd, Co, Ni, Fe, Au, Si, and Sn, or the element N is selected from two or more of Ti, Hf, Nb, Ta, Y, Sc, and Ga" are more conducive to further reducing the nucleation rate of the B2 phase and slowing down its growth rate, thereby effectively controlling and forming a fine and diffuse microstructure.

[0059] Furthermore, in the atomic percentage expression formula, 40≤a≤45, 40≤b≤45, 2≤c≤6, 6≤d≤8, and 1≤e≤8, which is beneficial to further improve the compressive plasticity, work hardening ability, critical formation size, and B2 phase dispersion degree of phase transformation toughened amorphous composite materials, and greatly expands the application range of amorphous composite materials.

[0060] As an example, the atomic percentage expression for phase transformation toughened amorphous composite materials can be (Zr 42 Ti5Hf1)(Cu 40.75 Ag5Co 0.5 Ni1Sn 0.75 Al4、(Zr 44 Ti2Hf 0.5 (Cu) 42.75 Ag5Co 0.5 Ni 0.5 Sn 0.75 Al4、(Zr 41.5 Ti5Hf1Nb 0.5 (Cu) 40.75 Ag5Co 0.5 Ni1Sn 0.75 Al4 or (Zr 42 Ti5Hf 0.5 Nb 0.5 (Cu) 41.5 Ag5Co 0.5 Ni 0.5 Sn 0.5 )Al4.

[0061] The aforementioned phase change toughened amorphous composite materials have good compressive plasticity and work hardening ability, as well as a large critical formation size, which greatly expands the application range of amorphous composite materials.

[0062] The phase change toughened amorphous composite material provided in this application has large dimensions, compressive plasticity, and work hardening ability. As an example, the phase change toughened amorphous composite material is columnar with a diameter ≥10mm and a compression ratio of 4-9%.

[0063] This application also provides a method for preparing the phase transformation toughened amorphous composite material provided above. Figure 1 A process flow diagram for preparing the phase transformation toughened amorphous composite material provided in this application is shown. Please refer to [link / reference]. Figure 1 The preparation methods of phase transformation toughened amorphous composite materials include:

[0064] S10, prepared according to the general formula expressed in atomic percentage.

[0065] In this application, all elements in the atomic percentage expression formula of the phase transformation toughened amorphous composite material are selected as high-purity elements, and the purity of the metal elements is ≥99.9%.

[0066] Before the raw materials are melted into master alloy ingots, the oxide layer and oil stains on the surface of the elemental materials need to be removed with fine sandpaper, and the materials need to be ultrasonically cleaned and dried for later use. This is to avoid the impurities in the master alloy ingot affecting the uniformity of the microstructure of the phase transformation toughened amorphous composite material.

[0067] Furthermore, the ultrasonic cleaning solution can be anhydrous ethanol.

[0068] S20, which melts the raw materials into master alloy ingots.

[0069] In this application, the steps for preparing the master alloy ingot include: melting the raw materials sequentially in order of decreasing melting point under vacuum and an inert atmosphere.

[0070] Melting the raw materials sequentially in order of decreasing melting point can prevent the lower melting point material from melting first and then coating the surface of the higher melting point material, which would result in insufficient melting of the higher melting point material. This is beneficial to improving the uniformity of mixing between the raw materials, and in turn, it is beneficial to further improve the compressive plasticity, work hardening ability, and critical formation size of the obtained phase transformation toughened amorphous composite material.

[0071] As an example, the raw materials can be melted to form a master alloy ingot using an electric arc melting method.

[0072] The process of "melting raw materials in order of decreasing melting point" can be achieved by placing the low-melting-point elemental ingots at the bottom of the electric arc furnace crucible and the high-melting-point elemental ingots at the top. Alternatively, the high-melting-point elements can be melted into a pre-alloy first, and then the pre-alloy can be mixed and melted with the remaining low-melting-point elements to form a master alloy ingot.

[0073] As an example, the raw materials contain elements with melting points above 2000°C, such as Hf, Nb, Ta and other high-melting-point elements. The high-melting-point elements such as Hf, Nb, Ta are first melted and prepared into a pre-alloy before being mixed and melted with other low-melting-point elements.

[0074] Furthermore, before smelting the raw materials, titanium ingots are smelted first to consume the residual oxygen in the system.

[0075] In this application, the raw materials are repeatedly melted at least four times, which helps to further improve the uniformity of the mixing between the raw materials.

[0076] In this application, the melting current for preparing the master alloy ingot is ≥240A, which is beneficial to ensure that the raw materials are fully melted and mixed evenly.

[0077] As an example, the vacuum degree for preparing the master alloy ingot is 5 × 10⁻⁶. -3 -5×10 -4 Pa, the inert atmosphere is high-purity argon, and the arc ignition melting time for titanium ingots is at least 2 minutes.

[0078] S30, melts the master alloy ingot into a liquid alloy.

[0079] The steps for melting the master alloy ingot into a liquid alloy include: arc melting the master alloy ingot with a current of ≥240A and holding it at that temperature for 5-20s under an inert atmosphere of 0.01-0.05MPa.

[0080] Under the above conditions, the raw materials can be fully melted and mixed evenly, which is beneficial to further improve the compressive plasticity, work hardening ability and critical formation size of the obtained phase change toughened amorphous composite material.

[0081] S40: The molten alloy is injected into the mold and then cooled.

[0082] In this application, the temperature of the mold is 10-25℃, which is conducive to the rapid solidification of the molten raw material mixture and the formation of amorphous phase and B2-CuZr crystalline phase during the solidification process. This is beneficial to further improve the compressive plasticity and work hardening ability of the phase transformation toughened amorphous composite material, and also to improve the critical formation size of the amorphous composite material, so that the size of the prepared amorphous composite material is larger, which greatly expands the application range of amorphous composite materials.

[0083] As an example, the temperature of the mold can be 10°C, 15°C, 18°C, 20°C, or 25°C, etc.

[0084] Furthermore, the mold is a copper mold. Copper molds have good thermal conductivity, which is conducive to the rapid solidification of the molten raw material mixture and the formation of amorphous phase and B2-CuZr crystalline phase during the solidification process. This helps to increase the critical formation size of amorphous composite materials, resulting in larger sizes of the prepared amorphous composite materials and greatly expanding the application range of amorphous composite materials.

[0085] Understandably, after melting the master alloy ingot into a liquid alloy, it is necessary to quickly inject the liquid alloy into the mold; otherwise, the liquid alloy may begin to solidify before being injected into the mold.

[0086] This application also provides the application of the phase change toughened amorphous composite material provided above in the preparation of harmonic reducer gears, 3C electronic structural parts, armor-piercing heads or armor plates.

[0087] Since the phase change toughened amorphous composite material provided in this application has high compressive plasticity and work hardening ability, and can also form columnar materials with diameters reaching the centimeter level, it is expected to be used in the preparation of harmonic reducer gears, 3C electronic structural parts, armor-piercing heads or armor plates.

[0088] Example 1

[0089] This embodiment provides a phase change toughened amorphous composite material and its preparation method. The atomic percentage expression of the phase change toughened amorphous composite material is (Zr 42 Ti5Hf1)(Cu 40.75 Ag5Co 0.5 Ni1Sn 0.75 Al4 was prepared using the following steps:

[0090] (1) After removing the oxide layer and oil stains on the surface of Zr, Ti, Hf, Cu, Ag, Co, Ni, Sn and Al with fine sandpaper, put them into a beaker, add anhydrous ethanol until the anhydrous ethanol submerges the above elemental raw materials, sonicate for 3 minutes and then dry for later use.

[0091] (2) The elemental raw materials obtained in step (1) are batched according to the general formula of atomic expression and placed in a vacuum arc melting furnace. The furnace cavity is then evacuated to a high vacuum of 5 × 10⁻⁶. -4 The process involves three Pa cycles, followed by the introduction of high-purity argon gas for purging. First, the titanium ingot is melted for 2 minutes to consume residual oxygen in the system. Then, Zr, Ti, and Hf are melted using a 240A melting current to form a ZrTiHf pre-alloy. Finally, Cu, Ag, Co, Ni, Sn, and Al are mixed with the ZrTiHf pre-alloy and repeatedly melted four times using a 240A melting current, each melting cycle lasting 120 seconds. The mixture is then cooled to obtain the master alloy ingot.

[0092] (3) Under argon protection at 0.04 MPa, the master alloy ingot obtained in step (2) was arc-melted using a melting current of 240 A and held for 10 s to obtain a liquid alloy. Then the liquid alloy was rapidly injected into a copper mold at 15 °C until it cooled and solidified to obtain a phase transformation toughened amorphous composite material.

[0093] Example 2

[0094] This embodiment provides a phase transformation toughened amorphous composite material and its preparation method. The difference between Embodiment 2 and Embodiment 1 is that the atomic percentage expression for the phase transformation toughened amorphous composite material and its preparation method in Embodiment 2 is (Zr 44 Ti2Hf 0.5 (Cu) 42.75 Ag5Co 0.5 Ni 0.5 Sn 0.75 )Al4.

[0095] Example 3

[0096] This embodiment provides a phase transformation toughened amorphous composite material and its preparation method. The difference between Example 3 and Example 1 is that the atomic percentage expression of the phase transformation toughened amorphous composite material and its preparation method in Example 3 is (Zr 41.5 Ti5Hf1Nb 0.5 (Cu) 40.75 Ag5Co 0.5 Ni1Sn 0.75 Al4, and in step (3), Zr, Ti, Hf and Nb are smelted into ZrTiHfNb pre-alloy, and Cu, Ag, Co, Ni, Sn and Al are mixed and smelted with ZrTiHfNb pre-alloy.

[0097] Example 4

[0098] This embodiment provides a phase transformation toughened amorphous composite material and its preparation method. The difference between Example 4 and Example 1 is that the atomic percentage expression for the phase transformation toughened amorphous composite material and its preparation method in Example 3 is (Zr 42 Ti5Hf 0.5 Nb 0.5 (Cu) 41.5 Ag5Co 0.5 Ni 0.5 Sn 0.5 Al4, and in step (3), Zr, Ti, Hf and Nb are smelted into ZrTiHfNb pre-alloy, and Cu, Ag, Co, Ni, Sn and Al are mixed and smelted with ZrTiHfNb pre-alloy.

[0099] Comparative Example 1

[0100] This comparative example provides an amorphous composite material and its preparation method. The atomic percentage expression for the amorphous composite material is Zr. 48 Cu 48 Al4 was prepared using the following steps:

[0101] (1) After removing the oxide layer and oil stains on the surface of Zr, Cu and Al elements with fine sandpaper, put them into a beaker, add anhydrous ethanol until the anhydrous ethanol submerges the above elemental raw materials, sonicate for 3 minutes and then dry for later use.

[0102] (2) The elemental raw materials obtained in step (1) are batched according to the general formula of atomic expression and placed in a vacuum arc melting furnace. The furnace cavity is then evacuated to a high vacuum of 5 × 10⁻⁶. -4 The process involves three Pa cycles, followed by the introduction of high-purity argon gas for purging. The titanium ingot is first melted for 2 minutes to consume the residual oxygen in the system. Then, Zr, Cu, and Al are melted and mixed using a melting current of 240A, and the process is repeated four times, with each melting cycle lasting 120 seconds. The resulting master alloy ingot is then cooled.

[0103] (3) Under argon protection at 0.04 MPa, the master alloy ingot obtained in step (2) was arc-melted using a melting current of 240 A and held for 10 s to obtain a liquid alloy. Then the liquid alloy was rapidly injected into a copper mold at 15 °C until it cooled and solidified to obtain a phase transformation toughened amorphous composite material.

[0104] Comparative Example 2

[0105] This comparative example provides an amorphous composite material and its preparation method. The atomic percentage expression of the amorphous composite material is (Zr 35 Ti 10 Hf3)(Cu 36 Ag1Co5Ni5Sn1)Al4 was prepared using the following steps:

[0106] (1) After removing the oxide layer and oil stains on the surface of Zr, Ti, Hf, Cu, Ag, Co, Ni, Sn and Al with fine sandpaper, put them into a beaker, add anhydrous ethanol until the anhydrous ethanol submerges the above elemental raw materials, sonicate for 3 minutes and then dry for later use.

[0107] (2) The elemental raw materials obtained in step (1) are batched according to the general formula of atomic expression and placed in a vacuum arc melting furnace. The furnace cavity is then evacuated to a high vacuum of 5 × 10⁻⁶. -4 The process involves three Pa cycles, followed by the introduction of high-purity argon gas for purging. First, the titanium ingot is melted for 2 minutes to consume residual oxygen in the system. Then, Zr, Ti, and Hf are melted using a 240A melting current to form a ZrTiHf pre-alloy. Finally, Cu, Ag, Co, Ni, Sn, and Al are mixed with the ZrTiHf pre-alloy and repeatedly melted four times using a 240A melting current, each melting cycle lasting 120 seconds. The mixture is then cooled to obtain the master alloy ingot.

[0108] (3) Under argon protection at 0.04 MPa, the master alloy ingot obtained in step (2) was arc-melted using a melting current of 240 A and held for 10 s to obtain a liquid alloy. Then the liquid alloy was rapidly injected into a copper mold at 15 °C until it cooled and solidified to obtain a phase transformation toughened amorphous composite material.

[0109] Experimental Example 1

[0110] The amorphous composite materials prepared in Examples 1-4 were characterized by X-ray diffraction patterns and SEM, respectively. The amorphous composite materials prepared in Comparative Examples 1-2 were characterized by X-ray diffraction patterns and optical microscopy, respectively. The X-ray diffraction patterns corresponding to Examples 1-4 and Comparative Examples 1-2 are shown below. Figure 2 , Figure 4 , Figure 6 , Figure 8 , Figure 10 as well as Figure 12 As shown, the SEM images corresponding to Examples 1-4 are respectively as follows: Figure 3 , Figure 5 , Figure 7 as well as Figure 9 As shown, the light micrographs corresponding to Comparative Examples 1-2 are respectively as follows: Figure 11 as well as Figure 13 As shown.

[0111] from Figure 2 ( Figure 2 The illustrations (which are macroscopic photographs of the material) show that the amorphous composite material prepared in Example 1 consists of an amorphous matrix and a B2-CuZr crystalline phase. Figure 3 It can be seen that the amorphous matrix of the amorphous composite material prepared in Example 1 contains a large amount of Zr5Sn3 nucleating agent, and the B2 crystalline phase is dispersed, with a size ranging from tens to 200 micrometers. The morphology of the B2 crystalline phase varies, exhibiting elliptical, square, and irregular edge shapes. This indicates that the amorphous composite material of Example 1 can effectively reduce the nucleation rate and growth rate of the B2 phase.

[0112] from Figure 4 ( Figure 4 The illustrations (which are macroscopic photographs of the material) show that the amorphous composite material prepared in Example 2 consists of an amorphous matrix, a B2-CuZr crystalline phase, and a B19' martensitic crystalline phase. Figure 5It can be seen that the amorphous matrix of the amorphous composite material prepared in Example 2 contains a large amount of Zr5Sn3 nucleating agent. Compared with Example 1, after the addition of Hf and Ni was reduced to 0.5 at.% in Example 2, the B2 crystal phase was more dispersed, uniform, and fine, with a size between tens and 200 micrometers. This indicates that the amorphous composite material of Example 2 can effectively reduce the nucleation rate and growth rate of the B2 phase, and can further reduce the nucleation rate and growth rate of the B2 phase compared with Example 1.

[0113] from Figure 6 ( Figure 6 The illustrations (which are macroscopic photographs of the materials) show that the amorphous composite material prepared in Example 3 consists of a large volume fraction of amorphous matrix and a small amount of B2-CuZr crystalline phase, indicating that Example 3 has a greater amorphous forming ability compared to Example 1. Figure 7 It can be seen that a large amount of Zr5Sn3 nucleating agent is distributed in the amorphous matrix of the amorphous composite material prepared in Example 3. Compared with Example 1, after adding Nb at 0.5 at.%, the B2 crystal phase exhibits an uneven substructure with dark gray and light gray characteristics. Irregular shell structures also appear at the edges and center of the B2 phase. The size of the B2 crystal phase ranges from tens to 200 micrometers, with cubic B2 phases being the most common. This indicates that the amorphous composite material of Example 3 can also effectively reduce the nucleation rate and growth rate of the B2 phase.

[0114] from Figure 8 ( Figure 8 The illustrations (which are macroscopic photographs of the material) show that the amorphous composite material prepared in Example 4 consists of an amorphous matrix and a B2-CuZr crystalline phase. Figure 9 It can be seen that the amorphous composite material prepared in Example 4 contains a large amount of Zr5Sn3 nucleating agent. Compared with Example 1, after adding Nb of 0.5 at.% and Hf and Ni of 0.5 at.%, the B2 crystal phase is basically cubic in shape, and the size of the B2 crystal phase is less than 200 micrometers, with most being tens of micrometers. The square B2 phase exhibits an uneven substructure with dark gray and light gray characteristics. The color of the B2 phase is lighter at the center and darker at the edges, showing an overall characteristic of bright center and dark edges. This indicates that the amorphous composite material of Example 4 can also effectively reduce the nucleation rate and growth rate of the B2 phase.

[0115] from Figure 10 It can be seen that the amorphous composite material prepared in Comparative Example 1 consists of the B2 phase (when the prepared size is < 6 mm) and the B19' phase (when the prepared size is 8 mm). Figure 11 It can be seen that in the amorphous composite material prepared in Comparative Example 1, the B2 phase has a relatively large size in the amorphous matrix with a diameter of 6 mm, and they are interconnected. Figure 11The inset above shows a macroscopic photograph of the material; it indicates that the amorphous composite material of Comparative Example 1 cannot effectively suppress the growth rate of the B2 phase, and once nucleated, it easily grows to a large size (200 micrometers). Meanwhile, the critical formation size of the amorphous composite material prepared in Comparative Example 1 is relatively small (≤6 mm). According to... Figure 11 The microstructure of the medium-conical sample shows that the volume fraction of the amorphous matrix is ​​small, the volume of the B2 phase is large, and the B2 phase is connected and grown.

[0116] from Figure 12 ( Figure 12 The illustrations (which are macroscopic photographs of the materials) show that the amorphous composite material prepared in Comparative Example 2 is mainly composed of the B2 phase at a diameter of 3.5 mm, while a small amount of AlTi2 phase precipitates at 5.2 mm. Figure 13 (Optical microscopy image at 3.5 mm diameter) It can be seen that in the amorphous composite material prepared in Comparative Example 2, at a diameter of 3.5 mm, the size of the B2 phase in the amorphous matrix is ​​relatively large, basically reaching 200 micrometers. At a larger preparation size (~4.2 mm), the B2 phase grows directly. This indicates that the amorphous composite material in Comparative Example 2 cannot effectively reduce the nucleation rate and growth rate of the B2 phase, and the critical formation size of the amorphous composite material is only 4.2 mm.

[0117] Experiment Example 2

[0118] The amorphous composite material prepared in Example 1 was cut into specimens with a diameter of φ1.5mm × 3mm, and the stress-strain curves of the specimens under compression were obtained. The results are as follows. Figure 14 As shown.

[0119] from Figure 14 It can be seen that the amorphous composite material prepared in Example 1 has at least 9% compressive plasticity and exhibits obvious work hardening behavior in the yield stage; indicating that the amorphous composite material prepared in Example 1 has good compressive plasticity and work hardening ability.

[0120] The amorphous composite material obtained in Example 2 was cut into specimens with a diameter of φ1.5mm × 3mm, and the stress-strain curves of the specimens under compression were obtained. The results are as follows. Figure 15 As shown.

[0121] from Figure 15 It can be seen that the amorphous composite material prepared in Example 2 has at least 4.7% compressive plasticity and exhibits obvious work hardening behavior in the yield stage; indicating that the amorphous composite material prepared in Example 2 has good compressive plasticity and work hardening ability.

[0122] The amorphous composite material obtained in Example 3 was cut into specimens with a diameter of φ1.5mm × 3mm, and the stress-strain curves of the specimens under compression were obtained. The results are as follows. Figure 16 As shown.

[0123] from Figure 16 It can be seen that the amorphous composite material prepared in Example 3 has at least 7% compressive plasticity and exhibits obvious work hardening behavior in the yield stage; indicating that the amorphous composite material prepared in Example 3 has good compressive plasticity and work hardening ability.

[0124] The amorphous composite material obtained in Example 4 was cut into specimens with a diameter of φ1.5mm × 3mm, and the stress-strain curves of the specimens under compression were obtained. The results are as follows. Figure 17 As shown.

[0125] from Figure 17 It can be seen that the amorphous composite material prepared in Example 4 has at least 4.1% compressive plasticity and exhibits obvious work hardening behavior in the yield stage; indicating that the amorphous composite material prepared in Example 4 has good compressive plasticity and work hardening ability.

[0126] The amorphous composite material prepared in Comparative Example 1 was cut into specimens with a diameter of φ1.5mm × 3mm, and the stress-strain curves of the specimens under compression were obtained. The results are as follows. Figure 18 As shown.

[0127] from Figure 18 It can be seen that the amorphous composite material prepared in Comparative Example 1 has at least 5% compressive plasticity and exhibits work hardening behavior in the yield stage; indicating that the amorphous composite material prepared in Comparative Example 1 has similar compressive plasticity and work hardening ability to Examples 1-4, but the amorphous composite material has a much smaller forming size than Examples 1-4, and the B2 phase is difficult to exhibit a uniform and dispersed distribution.

[0128] The amorphous composite material prepared in Comparative Example 2 was cut into specimens with a diameter of φ1.5mm × 3mm, and the stress-strain curves of the specimens under compression were obtained. The results are as follows. Figure 19 As shown.

[0129] from Figure 19 It can be seen that the amorphous composite material prepared in Comparative Example 2 has a compressive plasticity of 3.5%; indicating that the amorphous composite material prepared in Comparative Example 2 is difficult to obtain a phase transformation toughened amorphous composite material with large size and dispersed B2 phase distribution with the component percentage outside the scope of protection of this application, and the compressive plasticity and work hardening ability of the obtained amorphous composite material are similar to or slightly lower than those of the components protected in this application.

[0130] Experimental Example 3

[0131] Nanoindentation curves were performed on the amorphous composite material prepared in Example 4 with a certain B2 crystalline phase as the center. The hardness and modulus of the B2 crystalline phase and the amorphous matrix were characterized. The characterization results are as follows: Figure 20As shown; in the test, the matrix size was selected as 60μm×60μm, the applied force was 10mN, and the single-point spacing was 3μm.

[0132] exist Figure 20 From the modulus and hardness mapping diagrams, it can be seen that both reflect the same trend for the amorphous matrix and the B2 crystalline phase: the amorphous matrix has relatively high hardness and modulus values, approximately 8.9 GPa and 135 GPa, respectively, while the B2 crystalline phase has relatively low hardness and modulus values, approximately 5.9 GPa and 92 GPa, respectively. Within the B2 crystalline phase, the hardness and modulus values ​​in the central and peripheral regions also exhibit different ranges; that is, the central region of the B2 phase has lower modulus and hardness, while the peripheral region has higher modulus and hardness. This characteristic is consistent with... Figure 9 The results observed by scanning electron microscopy are consistent with the results, indicating that the amorphous composite material of Example 4 can also effectively reduce the nucleation rate and growth rate of the B2 phase.

[0133] Experiment Example 4

[0134] The amorphous composite materials prepared in Examples 1-4 and Comparative Examples 1-2 were characterized in terms of macroscopic dimensions, compressive plasticity, and work hardening properties. The characterization results are shown in Table 1.

[0135] Table 1

[0136]

[0137]

[0138] As shown in Table 1, the critical formation size of the phase transformation toughened amorphous composite material provided in this application is approximately 2 to 3 times that of Comparative Example 1 and Comparative Example 2. At such a large preparation size, it is possible to obtain compressive deformation capacity and work hardening capacity that are slightly higher than or similar to the comparative examples. This is due to the finer-sized and more dispersed B2 phase and the excellent amorphous matrix properties in the phase transformation toughened amorphous composite material provided in this application. Generally, the mechanical properties of an amorphous matrix are inversely proportional to its preparation size; that is, the larger the preparation size of the amorphous alloy, the worse its mechanical properties.

[0139] In summary, the phase change toughened amorphous composite material provided in this application is beneficial for forming columnar materials with diameters reaching the centimeter level, thus expanding the application range of amorphous composite materials, and maintaining high compressive plasticity and work hardening ability even at large sizes.

[0140] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A phase transformation toughened amorphous composite material, characterized in that, The atomic percentage expression for the phase transformation toughened amorphous composite material is (Zr 42 Ti5Hf1)(Cu 40.75 Ag5Co 0.5 Ni1Sn 0.75 Al4、(Zr 44 Ti2Hf 0.5 (Cu) 42.75 Ag5Co 0.5 Ni 0.5 Sn 0.75 Al4、(Zr 41.5 Ti5Hf1Nb 0.5 (Cu) 40.75 Ag5Co 0.5 Ni1Sn 0.75 Al4 or (Zr 42 Ti5Hf 0.5 Nb 0.5 (Cu) 41.5 Ag5Co 0.5 Ni 0.5 Sn 0.5 Al4; The phase change toughened amorphous composite material is columnar, with a diameter ≥10mm, and the B2 phase is uniformly dispersed and precipitated. The compression ratio of the phase change toughened amorphous composite material is 4-9%.

2. A method for preparing the phase transformation toughened amorphous composite material as described in claim 1, characterized in that, include: Under an inert atmosphere, the raw materials are melted and mixed according to the general formula expressed in terms of atomic percentages, then injected into a mold and cooled.

3. The preparation method according to claim 2, characterized in that, The temperature of the mold is 10-25℃.

4. The preparation method according to claim 2, characterized in that, The mold is a copper mold.

5. The preparation method according to claim 2, characterized in that, The melting and mixing steps include: placing the raw material in a vacuum arc melting furnace, evacuating the furnace cavity, and then introducing argon gas for gas exchange, melting the raw material to prepare a master alloy ingot; then, under an inert atmosphere of 0.01-0.05 MPa, using a current of ≥240 A to arc melt the master alloy ingot and hold it at that temperature for 5-20 seconds.

6. The preparation method according to claim 5, characterized in that, The steps for preparing the master alloy ingot include: melting the raw materials sequentially in order of decreasing melting point; The melting current for preparing the master alloy ingot is ≥240A; And / or, the vacuum degree for preparing the master alloy ingot is 5 × 10⁻⁶. -3 -5×10 -4 Pa.

7. The application of the phase change toughened amorphous composite material as described in claim 1 in the manufacture of harmonic reducer gears, 3C electronic structural components, armor-piercing heads or armor plates.

Citation Information

Patent Citations

  • Heavy size TRIP amorphous composite material and preparation method thereof

    CN104498844A